FORMS AND METHODS OF GAME TECHNOLOGIES IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Кадырова Сумбула Олимжоновна (American Journals, 2024)
Preschool education in the Republic of Uzbekistan is considered the basis of the education system, since the future masters of our future are brought up in these places, we must focus all our efforts and efforts on this system, today's education system meets world standards and modern requirements of the time. Taking into account the above, the modernization and reform of the methodology for managing the process of preschool education is of particular relevance. originating in the system of preschool education, in the everyday, pedagogical process of educational institutions.